Eine entropisch-ökonomische Analyse der "Routine" - Krcal, Hans-Christian (AWI discussion paper series, 2023)
‘Routine action’, a form to take action, is widely accepted in the economic field, because of its resource saving effect which contributes to average cost degression. However, from an entropic point of view, each form of acting requires decision making in regard to consumption of resources and causes entropic effects. Therefore, any kind of mechanistic resource management has to be avoided, even for routine action, when well-balanced economic-entropic actions, as to call them sustainable, are the objective. The paper shows how entropic and economic advantages and disadvantages of routine action can be brought together in a ratio to measure its sustainability’s relevance.
Keywords: Graue Literatur